Rethinking Rural Schooling in Laos: From a Deficit Perspective to Patchworked Mobilities, the State, and the Trope of Remoteness - Huijsmans, Roy (Journal of Political Sociology, 2025)
By combining insights from mobilities studies and the anthropology of the state and development, conceptual space is created for thinking about the social effects of the diverse sets of mobilities underpinning and related to rural schooling. This includes realising the state as a social relationship. Thereby, this article goes beyond a common deficit perspective on rural schooling. Drawing on ethnographic data, I show how diverse mobilities involving different sets of actors are valued and recognised differently, in part, because of their particular relation to constructs of remoteness, the state, and visions about rural futures.